The Importance Of Corporate Social Responsibility On Consumer Behaviour In Malaysia - Abd Rahim, Rahizah; Jalaludin, Farah Waheeda; Tajuddin, Kasmah (Asian Academy of Management (AAM), 2011)
Malaysian consumers should be more aware that, in pursuing their business objectives, corporations now bear more responsibility towards society and the environment. The awareness level has increased through better education and the increased influence of the media. Corporations also now believe that, to a certain extent, the degree of their involvement in corporate social responsibility (CSR) does have certain effect on consumers' buying behaviour. This paper aims to examine the influence of CSR on the buying behaviour of Malaysian consumers and whether they consider a corporation's CSR initiatives before making any purchase decisions of the products and services. The definition of CSR was adopted from Carroll's definition, which included economic, legal, ethical and philanthropic responsibilities. A total of 220 structured questions were distributed, with 193 returned for analysis. The results showed significant positive relationships between all of the variables used in measuring CSR and consumers' buying behaviour. Malaysian consumers' priority, however, seemed to be different from Carroll's pyramid, where, although economic responsibility remained the utmost priority, philanthropy stood second, followed by ethical and legal responsibility.